Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can someone please explain how to rewrite the expression $r+(3/2)s-(1/3)t$ in terms of $a, b,$ and $c$, where $r= \log (a), s=\log(b) \text{ and } t=2\log(c)$. The rewritten expression should be in the form of $\log (g(a,b,c))$

share|cite|improve this question
Use $\log(x)+\log(y)=\log(xy)$, $\log(x)-\log(y)=\log(x/y)$, $k\log(x)=\log(x^k)$. – lhf Aug 11 '11 at 11:46

I'm assuming that by "loge" you mean the natural logarithm with base $\mathrm e$, which I will write as "$\log$".

The key here are the relations $\log(xy)=\log x + \log y$ and $\log x^y=y\log x$. They allow you to rewrite as follows:

$$r+\frac32s-\frac13t=\log a+\frac32\log b-\frac132\log c=\log a+\log b^{3/2}+\log c^{-2/3}=\log(ab^{3/2}c^{-2/3})\;.$$

share|cite|improve this answer
Thanks joriki - appreciate your help – Michelle Aug 11 '11 at 12:00

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.